PERAN DESENTRALISASI FISKAL TERHADAP KINERJA EKONOMI DI KABUPATEN/KOTA PROVINSI JAWA TENGAH - Sasana, Hadi (Universitas Muhammdaiyah Surakarta, 2009)
This research is intended to examine the influence of fiscal decentralization on economic growth, poverty, employment, and welfare at regencies/municipalities level in Central Java Province. Research population consist of 29 regencies and 6 municipalities, employing secondary data from Central Bureau of Statistic of Central Java Province and regencies/municipalities level in Central Java Province within the period of 2001 up to 2005. Data analysis is conducted by using path analysis with AMOS program software. The results of this study indicate that, first fiscal decentralization has a positive and significant effect on economic growth. Second, economic growth has a positive and significant effect on employment rate. Third, economic growth has a negative and significant effect on poverty. Forth, economic growth has a positive and significant effect on welfare. Fifth, employment rate has a negative and significant effect on welfare. Sixth, poverty has a negative and significant effect on welfare at regencies/municipalities level in Central Java Province.